PERKAWINAN ENDOGAMI DALAM MASYARAKAT BATAK MANDAILING DI KEJORONGAN KASIK PUTIH KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Efri Yenti; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in Kejorongan Kasik Putih, sungai Aur district, Pasaman barat , West Sumatra. This research aims to find out how the process of marriage endogami and the role of law enforcement in custom petua marriage endogami. The theory used is the structural functional theory. Sample determination techniques generally purposive sampling, Researchers have set 5 pairs that did the marriage of endogami, 1 key informant i.e. King custom, and 2 person triangular i.e. petua customs and religious figures. Data analysis was done using descriptive and qualitative instrument data are observation, interview and documentation. From the results of the research in Batak mandailing people whose system of patrilineal activity is an exogamous marriage system has the provisions of the customs of the endogamous marriage or its fellow clan is strictly forbidden to To establish a marriage because in Batak mandailing society there is no belief of blood relations. There is a ban on endogamy marriage in order to avoid the marriage of siblings, avoiding the design of kinship relationships and maintaining embarrassment. However, for the couple who have already performed an endogamous marriage and still maintain a desire that is deemed to violate the rules of Customs, they are obliged to accept the customary sanctions imposed in Kejorongan Kasik Putih to The marriage can be accepted by the customs and Dalihan Natolu. The role of customary parenting on law enforcement and indigenous sanctions in endogamous marriages plays a role of giving, directing, guiding, leading so that society does not violate customary rules.  Keywords: Marriage Endogami, Batak Mandailing Society, Indigenous People